The effect of entrepreneurial trait in the relationship of technology entrepreneurship education and entrepreneurial behavior / Rohana Ngah ... [et al.] - Ngah, Rohana; Buyong, Siti Zahrah; Junid, Junainah; Mohd Lajin, Noor Faizah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Entrepreneurship has become an important national agenda especially in creating young entrepreneurs. This paper aims to determine the entrepreneurial behavior through technology entrepreneurship education and entrepreneurial personality trait of students from Science and Technology clusters. The purpose of technology entrepreneurship subject is to encourage students to embark on their entrepreneurship venture using technology. A total of five hundred and ninety-two usable questionnaires were collected at the end of the semester. Partial Least Square was utilized to explore the relationship of variables. Entrepreneurial personality trait mediated the relationship of technology entrepreneurship education and entrepreneurial behavior despite of lack of business exposure among students. Technology entrepreneurship education helps to foster the entrepreneurial behavior among students. In addition, knowing students’ entrepreneurial personality traits further strengthen the entrepreneurial behavior. Findings and recommendation of this study are discussed.